Tecido circence: a influência de um programa de intervenção motora no desenvolvimento motor, percepção de competência e ansiedade de crianças - Marroni, Paula Carolina Teixeira (2009)
The experimental and community study analysed the influence of a intervention program in Aerial Silk based on the Theory of Instruction (BRUNER, 2006) on motor development level, perceived competence and anxiety of young children. The study was composed by 16 children, (n=8) experimental group (G1) and (n=8) control group (G2). The pre-tests and post-tests instruments were: Movement ABC Test (Henderson e Sugden, 1992), Perceived Competence Scale (Harter, 1982), Pictorial Scale of Self Perceived Competence and Social Acceptance (Harter e Pike, 1984), Sport Anxiety Scale SAS-2 (SMITH, 2000), Daily Tasks Questionnaire (NETO, 1997) and Motor Intervention Program. The structure of the Motor Intervention Program was based on Bruner?sfour general requirements: predisposition, structure, sequence, and feedback. The experimental group (G1) took part of a two-sessions intervention process during 16 weeks on Aerial Silk wich has been filmed, monitored by observers who fullfilled na observation report and reported of daily routines used to data triangulation in order to cathegorize the Aerial Silk?s ements in na Aerial Adaptation Process. The quantitative data were analysed by descriptive statistcs (median and 1o and 3o quatiles), analitcs (Wilcoxon, Friedman, Mann-Whitney and Multiple Comparison tests), correlational (Spearman correlational quotient) and categorical content analysis. The results evidenced that for Motor ABC Test there were no significative differences between pre-tests and post-tests, demonstrating that the period of 16 weeks had no significant influence on motor development, suggesting the need of deep reflexion about tasks restriction and practice amount of habilities such as climbing on chindren?s daily basis. For Perceived Competence there was a significantdifference between pré-testand post-test for Morot Perceived Competence subscale, showing that motor intervention with positive encouragement can change children?s Perceived Competence. For State Anxiety there was a significative difference between pre-tests and posttests over the Worry subscale, demonstrating that children?s worry about practice reduced with motor experiences in Aerial Silk. The correlational analysis points that for this group of children there is a high and negative correlation between Perceived Competence and state anxiety, as well as Perceived Competence and Motor ABC Test datas. It is concluded that the motor intervention program in Aerial Silk based on Theory of Instruction (BRUNER, 2006) can influence positively on youn children?s perceived competence and anxiety, contributing to motor development.